Method for preparing rare earth doped garnet transparent ceramic through tape casting
By using rare earth-doped garnet powder, cardamide and dispersant, combined with casting molding and vacuum sintering processes, the problem of ceramic products being difficult to have high transparency, uniformity and density at the same time, achieving high efficiency preparation Quality transparent ceramic.
Patent Information
- Application Number
- CN202411537079.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art is difficult to meet the high transparency, uniformity and density of ceramic products at the same time, and traditional gel injection molding systems have toxicity problems and density reduction problems.
Ceramic slurry is prepared by rare earth-doped garnet powder, cardamide and dispersant. Transparent ceramics with high transparency and high density are prepared through casting and vacuum sintering processes.
The high transparency, uniformity and high density of ceramic products are achieved, and the density reduction and toxicity problems in traditional processes are avoided. The linear transmittance of the obtained ceramics can reach 66.8-73.2%, and the theoretical density can reach 99.90-99.99%.
Smart Images

Figure CN119409496A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional ceramics, and in particular relates to a method for preparing rare earth doped garnet transparent ceramics by tape casting. Background Art
[0002] In the early 1990s, Professor Mark.A.Janny and Professor O.Omattete of Oak Ridge National Laboratory in the United States invented the gel injection molding method, which is a molding technology for near-net-size ceramics. Its molding principle is to form a macromolecular network structure or a ceramic particle network structure through a chemical reaction inside the slurry, so that the ceramic slurry injected into the mold can be quickly solidified into a ceramic body. Gel injection molding requires the preparation of a ceramic slurry with low viscosity and high solid content. A catalyst, an initiator and an organic monomer are added to the slurry. The organic monomer in the slurry undergoes a polymerization reaction under the action of the initiator and the catalyst to form a three-dimensional network structure in situ. This network structure gel acts as a skeleton to fix the ceramic particles in the network, that is, in-situ curing molding; the first to be developed in this system is acrylamide monomer (AM), which needs to be added with an initiator potassium persulfate (APS) and a catalyst tetramethylethylenediamine (TEMED) for monomer polymerization. In addition, oxygen needs to be isolated during the polymerization process to prevent oxygen from preventing AM monomer polymerization, which brings trouble to the operation. At the same time, monomer acrylamide is harmful to the human nervous system. Therefore, it is of great value to study the non-toxic gel casting system.
[0003] Natural organic macromolecules such as agarose and pectin can form gels when undergoing physical or chemical changes. Sarkar et al. first proposed heat-resistant gels, using methylcellulose as a gelling agent. When heated above the gelling temperature, the methylcellulose completely dissolves, and then cools down to solidify. In recent years, many studies have begun to use polysaccharides to perform gel injection molding on ceramics. Fanelly et al. used agar for gel injection molding, heating up to melt, and cooling down to solidify. Millan et al. used carrageenan as a gelling agent, and Isabel Santacruz et al. used carrageenan and locust bean gum to perform gel injection molding. However, these gelling agents need to be cooled after heating to solidify and form a gel, resulting in the inability of the prepared products to simultaneously meet good transparency, uniformity and density. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for preparing rare earth doped garnet transparent ceramics by tape casting. The transparent ceramics prepared by the preparation method can have both high transparency and density, and excellent overall uniformity.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a transparent ceramic, comprising the following steps:
[0006] (1) Take the rare earth doped garnet powder, curdlan gum and dispersant, add water and carry out wet ball milling to obtain a ceramic slurry;
[0007] (2) After defoaming the ceramic slurry, use tape casting to obtain a green ceramic body;
[0008] (3) Debind the green ceramic body, and then sinter it in a vacuum environment to obtain the transparent ceramic.
[0009] Specifically, the transparent ceramic of the present invention uses rare earth doped garnet powder as the main raw material, adds a certain amount of curdlan gum organic monomer and dispersant to make a ceramic slurry; then places the ceramic slurry in a tape casting doctor blade hopper for tape casting to obtain a green body. Polymerization reaction occurs during the tape casting process of curdlan gum polymer single chains, turning single chain molecules into polymer high molecular gels. Since the gel body is a network macromolecular structure, the rare earth doped garnet powder is solidified in the network molecular structure, and the dissolved substances in the solvent will not migrate with the directional movement of the solvent during the drying process, thus maintaining the uniformity of the composition and structure of the green body, and also avoiding the defect that the density of the green body is reduced due to the addition of a large amount of organic binders and plasticizers in conventional tape casting, while being beneficial to the removal of pores in the green body during the subsequent vacuum sintering process, and then obtaining a ceramic product with high transparency and good overall uniformity.
[0010] At the same time, curdlan gum is a safe edible gel. It is insoluble in water and most organic solvents such as alcohol. The curdlan emulsion will solidify to form a gel when heated. The molecular formula of curdlan gum is (C 6 H 10 O 5 )n. Common coagulants need to be cooled after heating to solidify and form a gel, but curdlan gum is different. It gradually forms a gel when heated, and the curdlan gum will not melt even when the temperature continues to rise. It is a thermogel. The present invention makes full use of the gel characteristics of curdlan gum, combines tape casting to prepare a high-quality green ceramic body, and then obtains a highly transparent and highly dense rare earth doped garnet transparent ceramic through vacuum sintering.
[0011] Preferably, the chemical general formula of the rare earth doped garnet powder is: (A x B 1-x ) 3 Al 5 O 12 , where: A represents Ce, B represents Y or Lu, and 0 < x ≤ 0.01. That is, the rare earth doped garnet of the present invention is cerium doped yttrium aluminum garnet (YAG) or cerium doped lutetium aluminum garnet (LuAG).
[0012] Preferably, the preparation steps of the rare earth doped garnet powder are: according to the chemical formula (A x B 1-x ) 3 Al 5 O 12 Weigh CeO in a stoichiometric ratio 2 , Y 2 O 3 or Lu 2 O 3 、Al 2 O 3 , adding a sintering aid and a solvent, ball milling, drying, and calcining at 1200-1500° C. for 1-3 hours to obtain the rare earth-doped garnet powder.
[0013] Preferably, the sintering aid comprises tetraethyl orthosilicate (TEOS).
[0014] Preferably, the solvent comprises ethanol.
[0015] Preferably, the weight of the ethanol is 1-1.5 times that of the rare earth-doped garnet powder.
[0016] Preferably, the ball mill uses alumina grinding balls.
[0017] Preferably, the weight of the alumina grinding balls is 3.8-4.3 times that of the rare earth-doped garnet powder.
[0018] Preferably, the rotation speed of the ball mill is 60-70 r / min.
[0019] Preferably, the ball milling time is 24-48 hours.
[0020] Preferably, the dispersant is a polycarboxylic acid compound.
[0021] Further preferably, the dispersant is selected from DOLAPIX CE-64 produced by Zschimmer & Schwarz, Germany.
[0022] Specifically, polycarboxylic acid compounds are used as dispersants, and carboxylic acid anions are mainly dispersed into anionic groups in aqueous solution, which are adsorbed on the surface of rare earth-doped garnet powder particles to form electrostatic effects of mutual repulsion between like charges, so that the powder can be well dispersed in the aqueous solution slurry, thereby increasing the solid content of the slurry and the fluidity of the slurry, thereby increasing the density of the gel blank.
[0023] Preferably, the calcination temperature is 1350-1400°C.
[0024] Preferably, in step (1), the raw material components of the ceramic slurry include, by weight: 100 parts of rare earth-doped garnet powder, 0.5-2.5 parts of curdlan gum and 0.5-1.5 parts of dispersant.
[0025] Preferably, in step (1), the solid content of the ceramic slurry is 60-80wt%.
[0026] Preferably, in step (1), the pH of the ceramic slurry is 7-10.
[0027] Preferably, in step (2), the degassing is performed by centrifugal vacuum degassing, the vacuum degree is below -0.1 MPa, and the centrifugal speed is 600-1200 r / min.
[0028] Further preferably, the centrifugal speed program is: first centrifuge at a speed of 600-700 r / min for 20-40s; then increase the speed to 800-900 r / min for 80-90s; and then increase the speed to 1100-1200 r / min for 20-40s. Studies have found that the centrifugal speed program is more conducive to the discharge of bubbles.
[0029] Preferably, in step (2), the solidification temperature of the tape casting is 30-80°C.
[0030] Further preferably, the control procedure of the solidification temperature is: first adjust the temperature of the cast film belt to 60-80°C, rotate the film belt to make the ceramic slurry flow out from the scraper, and solidify the ceramic slurry; after the ceramic green body is solidified in situ, reduce the temperature to 30-40°C to slowly dry the moisture in the green body to prevent the ceramic green body from shrinking too quickly and causing cracking of the green body.
[0031] Preferably, in step (2), the moving speed of the scraper for tape casting is 1-2 mm / min.
[0032] Preferably, in step (3), the maximum temperature of the debinding is 700-800° C., so as to remove the curdlan gum and dispersant in the ceramic green body.
[0033] Further preferably, in step (3), the temperature regime for debinding is: firstly, heating from room temperature to 200-300°C at a rate of 0.5-1.5°C / min; then heating to 300-500°C at a rate of 0.5-1°C / min; then heating to 500-800°C at a rate of 0.5-1.5°C / min; and finally keeping the temperature for 2-5 hours. The main purpose of debinding is to remove organic substances such as curdlan gum and dispersant in the ceramic blank.
[0034] Preferably, in step (3), the maximum sintering temperature is 1400-1900°C.
[0035] Further preferably, in step (3), the sintering temperature regime is: firstly, heating from room temperature to 900-1000°C at a rate of 8-12°C / min; then heating to 1000-1400°C at a rate of 4-6°C / min, and keeping warm for 4-6 hours; then heating to 1400-1900°C at a rate of 1-3°C / min, and keeping warm for 8-10 hours; finally, cooling to 1100-1300°C at a rate of 4-6°C / min, and naturally cooling to room temperature.
[0036] Further preferably, in step (3), the maximum sintering temperature is 1750-1820°C.
[0037] Specifically, for ceramic products, their microstructure depends to a considerable extent on their thermal process, and the final microstructure is the result of the combined effect of the kinetic factors determined by the corresponding firing system and the thermodynamic factors determined by the chemical composition. In the initial stage of heating, the present invention heats up at a faster heating rate because the green body has not yet shrunk and the pores have not yet been eliminated. The second stage (900-1000°C) is the process of powder particles merging and growing to form grain boundaries, and the green body is also in a rapid shrinkage stage. Therefore, the growth rate of the grains should not be too fast, and a certain period of heat preservation is performed to prevent the pores from being covered inside the grains. The third stage (1400-1900°C) is the stage of eliminating residual pores in the grain boundary triangle area. In this process, the movement speed of the grain boundary atoms is accelerated, but at the same time, the migration speed of the grain boundary pores is greater than the migration speed of the grain boundaries. In order to prevent the grain boundaries from quickly crossing the pores to form closed pores in the crystal, making the ceramic opaque, the heating rate needs to be reduced and the heat preservation is performed for a sufficient time. At the same time, the cooling rate in the high temperature zone is controlled to obtain a transparent and dense ceramic product.
[0038] The second aspect of the present invention provides a transparent ceramic, which is prepared by the above-mentioned transparent ceramic preparation method, and the linear transmittance of the transparent ceramic is greater than 66%. The transparent ceramic prepared by the in-situ curing tape casting using polysaccharide curdlan gum as a gelling agent has high transparency.
[0039] Preferably, the linear transmittance of the transparent ceramic is 66.8-73.2%.
[0040] Preferably, the theoretical density of the transparent ceramic is >99.9%.
[0041] More preferably, the theoretical density of the transparent ceramic is 99.90-99.99%.
[0042] The third aspect of the present invention provides the use of the transparent ceramic.
[0043] Specifically, a lamp includes the transparent ceramic.
[0044] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0045] (1) The present invention uses rare earth doped garnet powder as the main raw material, adds a certain amount of curdlan gum organic monomer and dispersant to prepare ceramic slurry, and adopts tape casting to prepare transparent ceramics. The network macromolecular structure of curdlan gum is used to solidify the rare earth doped garnet powder in the network molecular structure. During the drying process, the dissolved matter in the solvent will not migrate with the directional movement of the solvent, thereby ensuring the uniformity of the composition and structure of the green body and improving the density of the green body, thereby preparing transparent ceramics with high transparency, high density and good overall uniformity.
[0046] (2) The present invention utilizes the thermal gelling properties of the non-toxic polysaccharide cardran gum to in-situ solidify and form a ceramic blank, and combines it with the tape casting process to solve the technical problems of the toxicity of the traditional gel system and the need to add a large amount of organic adhesives and plasticizers to reduce the density of the blank during tape casting, thereby simplifying the preparation process of transparent ceramics. The linear transmittance of the prepared transparent ceramics can reach 66.8-73.2%, and the theoretical density can reach 99.90-99.99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 XRD diagram of the rare earth-doped garnet powder prepared in Example 1-2;
[0048] Figure 2 This is a SEM image of the rare earth-doped garnet powder prepared in Example 1;
[0049] Figure 3 is a viscosity curve diagram of the ceramic slurry prepared in Examples 1, 3-4;
[0050] Figure 4 is a viscosity curve diagram of the ceramic slurry prepared in Examples 1, 5-7;
[0051] Figure 5 It is a linear transmittance curve graph of the transparent ceramics prepared in Examples 1, 5-7;
[0052] Figure 6 The linear transmittance curve of the transparent ceramics prepared in Comparative Examples 1-3;
[0053] Figure 7 The actual pictures are of the transparent ceramics prepared in Example 1 and Comparative Examples 1-3;
[0054] Figure 8 This is a physical picture of the transparent ceramic prepared in Example 8. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0056] Example 1
[0057] A method for preparing a transparent ceramic comprises the following steps:
[0058] (1) Weigh Y 2 O 3 Powder 674.043 g, Al 2 O 3 Powder 509.75g, CeO 2 5.164 g of powder, 3.567 g of sintering aid tetraethyl orthosilicate (TEOS), 1426.7 g of ethanol, and alumina grinding balls (weight is 4.3 times of the total weight of the powder) were added, and placed in a 5L nylon drum for mixed ball milling. The drum mixing speed was 65r / mim, and the ball milling was carried out for 36 hours; then the ball-milled slurry was placed in an oven and baked at 100°C for 2 hours, and the ethanol was evaporated to obtain a mixed ceramic powder; after grinding and sieving the ceramic powder, it was calcined at 1350°C in air for 2 hours to remove the organic additives in the powder to obtain cerium-doped yttrium aluminum garnet powder.
[0059] (2) Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 2 g of DOLAPIX CE-64 dispersant (the amount added is 1.0 wt% of the cerium-doped yttrium aluminum garnet powder), and 1 g of Curdlan gum (the amount added is 0.5 wt% of the cerium-doped yttrium aluminum garnet powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0060] (3) The ceramic slurry prepared in step (2) is placed in an open plastic container, and then placed on a centrifugal vacuum degassing machine for degassing. During the high-speed centrifugation process, the vacuum degree reaches below -0.1Mpa, and vacuum degassing is performed. The centrifugal speed program is: first centrifuge at a speed of 600r / min for 30s; then increase the speed to 900r / min for centrifugation for 90s; then increase the speed to 1200r / min for centrifugation for 30s. After breaking the vacuum, take out the ceramic slurry and add it to the hopper of the casting machine to prepare for gel casting to form ceramic blanks. Adjust the temperature of the casting film belt to 60℃-80℃, and the scraper movement speed to 1-2mm / min, so that the cardlan glue forms a hot gel in situ solidified ceramic powder in this temperature range. As the film belt moves the gel blank to the temperature range of 30-40℃, the ceramic blank is slowly dried to prevent the ceramic blank from shrinking too fast and causing the blank to crack, thereby obtaining a ceramic blank.
[0061] (4) The ceramic blank obtained in step (3) needs to be subjected to a debinding treatment. The debinding temperature regime is as follows: first, the temperature is raised from room temperature to 300°C at a rate of 1°C / min; then, the temperature is raised to 400°C at a rate of 0.5°C / min; then, the temperature is raised to 800°C at a rate of 1°C / min, and the temperature is kept at this temperature for 2 hours; and the ceramic blank is naturally cooled in the furnace. The debinding ceramic blank is placed in a vacuum furnace and heated in a vacuum atmosphere (vacuum degree 3.5×10 -3 The sintering temperature system is: firstly, the temperature is raised to 1000°C at a heating rate of 10°C / min, then the temperature is raised to 1450°C at a heating rate of 5°C / min, and the temperature is kept for 5 hours, then the temperature is raised to 1750°C at a heating rate of 2°C / min, and the temperature is kept for 10 hours, and finally the temperature is lowered to 1200°C at a cooling rate of 5°C / min, and the temperature is naturally cooled to room temperature. After grinding and polishing, the Ce:YAG transparent ceramic of this embodiment is obtained.
[0062] Example 2
[0063] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (1) is changed. The specific steps are as follows:
[0064] (1) Weigh Y 2 O 3 Powder 674.043 g, Al 2 O 3 Powder 509.75g, CeO 25.164 g of powder, 3.567 g of sintering aid tetraethyl orthosilicate (TEOS), 1426.7 g of ethanol, and alumina grinding balls (weight is 4.3 times of the total weight of the powder) were added, and placed in a 5L nylon drum for mixed ball milling. The drum mixing speed was 65r / mim, and the ball milling was carried out for 36 hours. The ball-milled slurry was then placed in an oven and baked at 100°C for 2 hours. The ethanol was evaporated to obtain a mixed ceramic powder. The ceramic powder was ground and sieved, and then calcined in air at 1400°C for 2 hours to remove organic additives in the powder to obtain cerium-doped yttrium aluminum garnet powder.
[0065] Example 3
[0066] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (2) is changed. The specific steps are as follows:
[0067] Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 1 g of DOLAPIX CE-64 dispersant (the amount added is 0.5 wt% of the powder), and 1 g of curdlan gum (the amount added is 0.5 wt% of the powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0068] Example 4
[0069] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (2) is changed. The specific steps are as follows:
[0070] Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 3 g of DOLAPIX CE-64 dispersant (the amount added is 1.5 wt% of the powder), and 1 g of curdlan gum (the amount added is 0.5 wt% of the powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0071] Example 5
[0072] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (2) is changed. The specific steps are as follows:
[0073] Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 2 g of DOLAPIX CE-64 dispersant (the amount added is 1.0 wt% of the powder), and 2 g of curdlan gum (the amount added is 1 wt% of the powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0074] Example 6
[0075] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (2) is changed. The specific steps are as follows:
[0076] Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 2 g of DOLAPIX CE-64 dispersant (the amount added is 1.0 wt% of the powder), and 3 g of curdlan gum (the amount added is 1.5 wt% of the powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0077] Example 7
[0078] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (2) is changed. The specific steps are as follows:
[0079] Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 2 g of DOLAPIX CE-64 dispersant (the amount added is 1.0 wt% of the powder), and 5 g of curdlan gum (the amount added is 2.5 wt% of the powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0080] Example 8
[0081] A method for preparing a transparent ceramic comprises the following steps:
[0082] (1) Weigh Lu 2 O 3 Powder 1126.26g, Al 2 O 3 Powder 509.75g, CeO 2 5.164 g of powder, 3.567 g of sintering aid tetraethyl orthosilicate (TEOS), 1635.7 g of ethanol, and alumina grinding balls (weight is 3.8 times of the total weight of the powder) are added, and placed in a 5L nylon drum for mixed ball milling, the drum mixing speed is 65r / mim, and the ball milling is carried out for 36 hours; then the mixed powder slurry is placed in an oven and baked at 100°C for 2 hours, and the ethanol is evaporated to obtain a mixed ceramic powder; after the powder is ground and sieved, it is calcined in air at 1400°C for 2 hours to remove the organic additives in the powder to obtain cerium-doped lutetium aluminum garnet powder.
[0083] (2) Weigh 200 g of the lutetium-doped yttrium aluminum garnet powder prepared in step (1), add 80 g of deionized water, 2 g of DOLAPIX CE-64 dispersant (the amount added is 1.0 wt% of the lutetium-doped yttrium aluminum garnet powder), and 3 g of curdlan gum (the amount added is 1.5 wt% of the lutetium-doped yttrium aluminum garnet powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0084] (3) The ceramic slurry prepared in step (2) is placed in an open plastic container, and then placed on a centrifugal vacuum degassing machine for degassing. During the high-speed centrifugation process, the vacuum degree reaches below -0.1Mpa, and vacuum degassing is performed. The centrifugal speed program is: first centrifuge at a speed of 600r / min for 30s; then increase the speed to 900r / min for centrifugation for 90s; then increase the speed to 1200r / min for centrifugation for 30s. After breaking the vacuum, take out the ceramic slurry and add it to the hopper of the casting machine to prepare for gel casting to form ceramic blanks. Adjust the temperature of the casting film belt to 60℃-80℃, and the scraper movement speed to 1-2mm / min, so that the cardlan glue forms a hot gel in situ solidified ceramic powder in this temperature range. As the film belt moves the gel blank to the temperature range of 30-40℃, the ceramic blank is slowly dried to prevent the ceramic blank from shrinking too fast and causing the blank to crack, thereby obtaining a ceramic blank.
[0085] (4) The ceramic blank obtained in step (3) needs to be subjected to a debinding treatment. The debinding temperature regime is as follows: first, the temperature is raised from room temperature to 300°C at a rate of 1°C / min; then, the temperature is raised to 400°C at a rate of 0.5°C / min; then, the temperature is raised to 800°C at a rate of 1°C / min, and the temperature is kept at this temperature for 2 hours; and the ceramic blank is naturally cooled in the furnace. The debinding ceramic blank is placed in a vacuum furnace and heated in a vacuum atmosphere (vacuum degree 3.5×10 -3 The sintering temperature system is: firstly, the temperature is raised to 1000°C at a heating rate of 10°C / min, then the temperature is raised to 1450°C at a heating rate of 5°C / min, and the temperature is kept for 5 hours, then the temperature is raised to 1750°C at a heating rate of 2°C / min, and the temperature is kept for 10 hours, and finally the temperature is lowered to 1200°C at a cooling rate of 5°C / min, and the temperature is naturally cooled to room temperature. After grinding and polishing, the Ce:LuAG transparent ceramic of this embodiment is obtained.
[0086] Comparative Example 1
[0087] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (2) is changed. The specific steps are as follows:
[0088] (2) Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 2 g of DOLAPIX CE-64 dispersant (the amount added is 1.0 wt% of the cerium-doped yttrium aluminum garnet powder), and 1 g of gellan gum (the amount added is 0.5 wt% of the cerium-doped yttrium aluminum garnet powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0089] Comparative Example 2
[0090] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (2) is changed. The specific steps are as follows:
[0091] (2) Weigh 200 g of the cerium-doped yttrium aluminum garnet powder prepared in step (1), add 200 g of deionized water, 2 g of ammonium citrate dispersant (the amount added is 1.0 wt% of the cerium-doped yttrium aluminum garnet powder), and 1 g of carrageenan (the amount added is 0.5 wt% of the cerium-doped yttrium aluminum garnet powder), adjust the pH value to 9 with ammonia water, and ball mill for 12 hours to obtain a ceramic slurry.
[0092] Comparative Example 3
[0093] Referring to the preparation method of the transparent ceramic preparation method of Example 1, only step (4) is changed. The specific steps are as follows:
[0094] (4) The ceramic blank obtained in step (3) needs to be subjected to a debinding treatment. The debinding temperature regime is as follows: first, the temperature is raised from room temperature to 300°C at a rate of 1°C / min; then, the temperature is raised to 400°C at a rate of 0.5°C / min; then, the temperature is raised to 800°C at a rate of 1°C / min, and the temperature is kept at this temperature for 2 hours; and the ceramic blank is naturally cooled in the furnace. The debinding ceramic blank is placed in a vacuum furnace and heated in a vacuum atmosphere (vacuum degree 3.5×10 -3 The sintering temperature is as follows: the temperature is raised to 1750°C at a heating rate of 10°C / min, and the temperature is kept for 10 hours, and the temperature is naturally cooled to room temperature. After grinding and polishing, the Ce:YAG transparent ceramic of this comparative example is obtained.
[0095] Performance Testing
[0096] 1. Phase analysis
[0097] Figure 1 The XRD patterns of the cerium-doped yttrium aluminum garnet powders prepared in Example 1 and Example 2 are shown in FIG. Figure 1 It can be seen that the diffraction peaks of the cerium-doped yttrium aluminum garnet powder prepared by calcining at 1350°C and 1400°C for 2 hours all correspond to the cubic YAG crystal phase, and no intermediate transition phase YAP or YAM appears, indicating that the oxide in the raw material has been completely reacted under this temperature condition.
[0098] 2. Microscopic morphology
[0099] Figure 2 This is a SEM image of the cerium-doped yttrium aluminum garnet powder prepared in Example 1. Figure 2 It can be seen that the particle size distribution of the powder particles is uniform and the dispersion is good without obvious agglomeration.
[0100] 3. Viscosity of ceramic slurry
[0101] Figure 3 is the viscosity curve of the ceramic slurry prepared in Examples 1 and 3-4, Figure 3It can be seen that when 0.5 wt % of Curdlan gum is added, 0.5-1.5 wt % of DOLAPIX CE-64 dispersant is added respectively, and the viscosity of the prepared ceramic slurry is 5-15 Pa·S.
[0102] Figure 4 is the viscosity curve of the ceramic slurry prepared in Examples 1, 5-7, Figure 4 It can be seen that when 1.0 wt% of DOLAPIX CE-64 dispersant is added, 0.5-2.5 wt% of Curdlan gum is added respectively, and the viscosity of the prepared ceramic slurry is 10-20 Pa·S. At this viscosity difference, the slurry is easy to flow and form.
[0103] 4. Linear transmittance
[0104] According to the standard GB / T 7962.12-1987 colorless optical glass test method, the linear transmittance of the transparent ceramic samples prepared in Examples 1, 5-7 was measured, and the Archimedean drainage method was used to test the test density of the samples and the theoretical density of the ceramics for comparison. The theoretical density of the samples was calculated, and the results are shown in Tables 1 and Figure 5-6 shown.
[0105] Table 1:
[0106] sample Linear transmittance (%) Theoretical density (%) Example 1 66.8 99.93 Example 5 70.3 99.95 Example 6 73.2 99.99 Example 7 68.4 99.90 Comparative Example 1 37.5 99.83 Comparative Example 2 34.7 99.75 Comparative Example 3 33.0 99.72
[0107] From Table 1 and Figure 5-6 It can be seen that the linear transmittance of the transparent ceramic samples prepared in Examples 1 and 5-7 can reach 66.8-73.2%, and the theoretical density can reach more than 99.90%, with the characteristics of high transparency and high density, and the transparency and density of Examples 2-4 are similar to those of Examples 1 and 5-7. Compared with Example 1, the linear transmittance and theoretical density of the fluorescent transparent ceramics prepared in Comparative Examples 1-3, which use different colloids, dispersants and sintering systems, have decreased to a large extent. This shows that the performance of the transparent ceramics of the present invention is closely related to the selection of colloids and dispersants, as well as the sintering system.
[0108] 5. Uniformity
[0109] Figure 7 and Figure 8 The actual pictures of the transparent ceramics prepared in Example 1, Comparative Examples 1-3 and Example 8 are shown in FIG. Figure 7-8 It can be seen that the ceramic products prepared by the preparation method of the present invention in Example 1 and Example 8 have good transparency and no obvious bubbles. However, the ceramic products prepared by Comparative Examples 1-3 have obvious fogging and obvious bubbles, and poor transparency and uniformity due to the use of other similar gel raw materials and dispersants, as well as non-gradient temperature sintering systems.
[0110] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing a transparent ceramic, characterized in that: The following steps are involved: (1) taking rare earth-doped garnet powder, curdlan gum and a dispersant, adding water and performing wet ball milling to prepare a ceramic slurry; (2) after degassing the ceramic slurry, tape casting is used to obtain a ceramic green body; (3) Debinding the ceramic green body, and then sintering it in a vacuum environment to obtain the transparent ceramic.
2. The method for preparing transparent ceramics according to claim 1, characterized in that: The chemical formula of the rare earth doped garnet powder is: x B 1-x )3Al5O 12 , where: A represents Ce, B represents Y or Lu, 0 <x≤0.01。 3. The method for preparing transparent ceramics according to claim 2, characterized in that: The preparation steps of the rare earth doped garnet powder are as follows: x B 1-x )3Al5O 12 CeO2, Y2O3 or Lu2O3, Al2O3 are weighed in a stoichiometric ratio, a sintering aid and a solvent are added, and the mixture is ball-milled, dried, and calcined at 1200-1500° C. for 1-3 hours to obtain the rare earth-doped garnet powder.
4. The method for preparing transparent ceramics according to claim 3, characterized in that: The sintering aid includes tetraethyl orthosilicate; and / or, the solvent includes ethanol.
5. The method for preparing transparent ceramics according to claim 1, characterized in that: The dispersant is a polycarboxylic acid compound.
6. The method for preparing transparent ceramics according to claim 1, characterized in that: In step (1), the raw material components of the ceramic slurry include, by weight: 100 parts of rare earth-doped garnet powder, 0.5-2.5 parts of curdlan gum and 0.5-1.5 parts of dispersant; and / or the solid content of the ceramic slurry is 60-80wt%; and / or the pH of the ceramic slurry is 7-10.
7. The method for preparing transparent ceramics according to claim 1, characterized in that: In step (2), the solidification temperature of the tape casting is 30-80°C; and / or the moving speed of the scraper of the tape casting is 1-2 mm / min.
8. The method for preparing transparent ceramics according to claim 1, characterized in that: In step (3), the maximum temperature of the debinding is 700-800°C; and / or the maximum temperature of the sintering is 1400-1900°C.
9. A transparent ceramic, characterized in that: The transparent ceramic is prepared by the preparation method of any one of claims 1 to 8, wherein the linear transmittance of the transparent ceramic is greater than 66%; and / or the theoretical density of the transparent ceramic is greater than 99.9%.
10. A lamp, characterized in that: Comprising the transparent ceramic according to claim 9.
Citation Information
Patent Citations
Method for preparing Re:YAG polycrystalline transparent ceramic by using different molding modes
CN102060540A
Method for preparing yttrium aluminum garnet-based transparent ceramic through aqueous tape casting
CN103508729A
Method for preparing yttrium aluminium garnet transparent ceramic with composite structure
CN103626487A
Zirconia ceramic bearing preparation method based on gel casting technology
CN105347790A
Preparation method of yttrium aluminum garnet transparent ceramic
CN109574649A
Cited By
Diamond-silicon carbide composite material and non-toxic gel tape casting-reactive infiltration preparation method thereof
CN122301557A
